Penggunaan Media Konkret Terhadap Keaktifan Belajar Pembelajaran Matematika Kelas II SD Supriyadi 02 Semarang - Nur Rohmawati; Muhammad Prayito; Kartinah Kartinah; Ranto Netty Sofiati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of this study is to determine the use of concrete media for the activeness of student learning in mathematics learning grade IIb SD Supriyadi 02 Semarang. This type of research is descriptive qualitative research. This study used observation and interview techniques in data collection. The results showed that students actively learn in learning mathematics using concrete objects. In mathematics learning, learners are interested and learners are engaged in learning, as well as listening more and paying attention to what the teacher is conveying. This in learning situations shows an active, creative, and fun atmosphere. Active, creative, and fun learning if carried out continuously, it can increase students' interest in mathematics learning so that learning will be achieved. It is hoped that researchers can provide theoretical as well as practical benefits for the development of education, especially those related to the development of education in elementary schools. Learners can be seen listening to math learning in earnest. Based on the results of observations and interviews, students pay attention, listen, write, actively ask and answer, and do problems so that students feel happy in learning using concrete media in mathematics learning.